2002
DOI: 10.3386/w8918
|View full text |Cite
|
Sign up to set email alerts
|

Remedial Education and Student Achievement: A Regression-Discontinuity Analysis

Abstract: As standards and accountability have become an increasingly prominent feature of the educational landscape, educators have relied more on remedial programs such as summer school and grade retention to help low-achieving students meet minimum academic standards. Yet the evidence on the effectiveness of such programs is mixed, and prior research suffers from selection bias. However, recent school reform efforts in Chicago provide an opportunity to examine the causal impact of these remedial education programs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
218
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(229 citation statements)
references
References 3 publications
5
218
2
4
Order By: Relevance
“…What policies work to increase local labor supply quality? Policies with good research evidence of success include: high-quality preschool (Bartik 2011;Camilli et al 2010;Heckman 2006); mandatory summer school (Jacob and Lefgren 2004); high school career academies (Kemple and Willner 2008); improving teacher quality (Chetty, Friedman, and Rockoff 2011); demandoriented job training (Hollenbeck andHuang 2006, 2008). This research evidence includes both random assignment experiments, frequently with long-term follow-up on adult outcomes, as well as nonexperimental studies that arguably have very good comparison groups.…”
Section: Research Needs For Economic Development 553mentioning
confidence: 99%
“…What policies work to increase local labor supply quality? Policies with good research evidence of success include: high-quality preschool (Bartik 2011;Camilli et al 2010;Heckman 2006); mandatory summer school (Jacob and Lefgren 2004); high school career academies (Kemple and Willner 2008); improving teacher quality (Chetty, Friedman, and Rockoff 2011); demandoriented job training (Hollenbeck andHuang 2006, 2008). This research evidence includes both random assignment experiments, frequently with long-term follow-up on adult outcomes, as well as nonexperimental studies that arguably have very good comparison groups.…”
Section: Research Needs For Economic Development 553mentioning
confidence: 99%
“…Alternately, several studies indicated that making students repeat a grade seemed to boost their test scores or grades, at least temporarily (e.g., Alexander, Entwisle, & Dauber, 1994;Pierson & Connell, 1992). More recent retention studies of comparable research quality also indicate that retained students obtained higher test scores than low-performing socially promoted students ( Jacobs & Lefgren, 2004;Karweit, 1999;Lorence, Dworkin, Toenjes, & Hill, 2002;Pomplun, 1988).…”
Section: Conflicting Conclusionmentioning
confidence: 99%
“…Regression discontinuity analysis has several assumptions. First, unobserved characteristics of an individual must vary continuously with the observed characteristic used to identify the cutoff (Jacobs & Lefgren, 2002). Second, the treatment and control groups must both come from a single continuous pretest distribution and the division between groups must be determined by a cutoff.…”
Section: Detectionmentioning
confidence: 99%
“…The authors identified positive effects of prekindergarten attendance on children's achievement outcomes. Jacobs and Lefgren (2002) examined the impact of summer school on students' math and reading skills by assigning students to summer school based on pretest measures of reading and math and then comparing posttest reading and math scores of the treatment and control groups. The authors found that summer school increased children's subsequent reading and mathematics scores.…”
Section: Detectionmentioning
confidence: 99%